Evaluation of the diagnostic accuracy and cost of different methods for the assessment of severe anaemia in hospitalised children in Eastern Uganda [version 2; peer review: 3 approved] - Peter Olupot-Olupot; Natalie Prevatt; Charles Engoru; Julius Nteziyaremye; Denis Amorut; Martin Chebet; Tonny Senyondo; Paul Ongodia; Carolyne M. Ndila; Thomas N. Williams; Kathryn Maitland (Wellcome Open Research, 2019)
Background: Severe anaemia in children requiring hospital admission is a major public health problem in malaria-endemic Africa. Affordable methods for the assessment of haemoglobin have not been validated against gold standard measures for identifying those with severe anaemia requiring a blood transfusion, despite this resource being in short supply. Methods: We conducted a prospective descriptive study of hospitalized children aged 2 months – 12 years at Mbale and Soroti Regional Referral Hospitals, assessed to have pallor at triage by a nurse and two clinicians. Haemoglobin levels were measured using the HemoCue ® Hb 301 system (gold standard); the Haemoglobin Colour Scale; Colorimetric and Sahli’s methods. We report clinical assessments of the degree of pallor, clinicians’ intention to transfuse, inter-observer agreement, limits of agreement using the Bland-Altman method, and the sensitivity and specificity of each method in comparison to HemoCue ® Results: We recruited 322 children, clinically-assessed by the admitting nurse (n=314) as having severe (166; 51.6%), moderate (97; 30.1%) or mild (51; 15.8%) pallor. Agreement between the clinicians and the nurse were good: Clinician A Kappa=0.68 (0.60–0.76) and Clinician B Kappa=0.62 (0.53–0.71) respectively ( P<0.0001 for both). The nurse, clinicians A and B indicated that of 94/116 (81.0%), 83/121 (68.6%) and 93/120 (77.5%) respectively required transfusion. HemoCue ® readings indicated anaemia as mild (Hb10.0–11.9g/dl) in 8/292 (2.7%), moderate (Hb5.0–9.9g/dl) in 132/292 (45.2%) and severe (Hb<5.0g/dl) in 152/292 (52.1%). Comparing to HemoCue® the Sahli’s method performed best in estimation of severe anaemia, with sensitivity 84.0% and specificity 87.9% and a Kappa score of  0.70 (0.64–0.80). Conclusions: Clinical assessment of severe pallor results has a low specificity for the diagnosis of severe anaemia. To target blood transfusion Hb measurement by either Hemocue® or Sahli’s method for the cost of USD 4 or and USD 0.25 per test, respectively would be more cost-effective.